Dynamic weight-bearing test during jumping: A sensitive outcome measure of chronic osteoarthritis pain in rats. Issue 9 (September 2021) - Westhof, Andreas; Kleinschmidt-Doerr, Kerstin; Michaelis, Martin; Brenneis, Christian
Abstract: Pain due to osteoarthritis (OA) often occurs during locomotion in the vertical direction when joints are subjected to high mechanical load, e.g. during standing up from a chair or using stairs. To investigate joint pain in OA rat models, dynamic weight-bearing or gait analysis is traditionally conducted during horizontal walking on a flat surface. However, in chronic models of OA, which are of particular translational relevance for the disease, differences in the readouts between OA and control rats are often weak and of high variability leading to an insufficient assay window for drug profiling. To measure pain-related symptoms more sensitively, we conducted a dynamic weight-bearing test in the moment of a strong voluntary mechanical load. For that, we permanently housed rats in a four-story rat colony cage (RCC) and determined hind paw forces during voluntary jumping from one level to the next. This outcome measure was named jump incapacitance. After inducing OA by destabilizing the medial meniscus (DMM), we found that during jumps the average ipsilateral over contralateral hind paw forces were significantly reduced compared with healthy controls (jump incapacitance) from early- (day 7) to late-stage disease (day 90). An intra-articular injection of Zilretta (triamcinolone acetonide extended-release injectable suspension) attenuated OA-induced jump incapacitance after 8 days compared with DMM rats receiving vehicle (p = 0.069). In contrast, a CatWalk test for gait disturbance failed to detect any significant alterations in the chronic course of the DMM model. In conclusion, the dynamic weight-bearing test during jumping represents a novel method to characterize joint pain symptoms even in a slowly progressive OA rat model. It is sensitive, observer independent, relates to clinically relevant endpoints and demonstrates backtranslation of a drug that is approved for the treatment of OA knee pain. Abstract : Osteoarthritis, Weight bearing, Pain, Behavior test, Destabilization of the medial meniscus (DMM).